MODERN CONCEPT OF RURAL TOURISM DEVELOPMENT (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
The article is devoted to the modern concept of rural tourism development. Also, the article describes the development of rural tourism based on the experience of the developing countries of Europe.